The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1523/jneurosci.4045-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Augmentation Modulates Visual Task Performance in Sleep-Deprived Young Adults

Abstract: Using 24 h of total sleep deprivation to perturb normal cognitive function, we conducted a double-blind, placebo-controlled crossover study to evaluate the effect of the acetylcholinesterase inhibitor, donepezil, on behavioral performance and task-related brain activation in 28 healthy, young, adult volunteers. The behavioral tasks involved the parametric manipulation of visual short-term memory load and perceptual load in separate experiments indirectly evaluating attention. Sleep deprivation significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 64 publications
6
72
0
Order By: Relevance
“…However, as pointed out earlier, there was no significant relationship between state-related change in activation and task difficulty. Similar findings have been reported in experiments evaluating SD-related decline in visual short term memory capacity (Chee and Chuah, 2007), visual tracking (Tomasi et al, 2009) and the effect of cholinergic augmentation on performance (Chuah and Chee, 2008).…”
Section: Vulnerable Persons Are Unable To Increase Fronto-parietal Acsupporting
confidence: 86%
“…However, as pointed out earlier, there was no significant relationship between state-related change in activation and task difficulty. Similar findings have been reported in experiments evaluating SD-related decline in visual short term memory capacity (Chee and Chuah, 2007), visual tracking (Tomasi et al, 2009) and the effect of cholinergic augmentation on performance (Chuah and Chee, 2008).…”
Section: Vulnerable Persons Are Unable To Increase Fronto-parietal Acsupporting
confidence: 86%
“…It also has a vascular action by dilating cerebral parenchymal arterioles via the activation of neuronal nitric oxide enzymes (Nakahata et al 2008). In normal subjects, cholinergic augmentation with donepezil improves cognitive functions linked with language, such as learning and memory encoding (Yesavage et al 2002;Grön et al 2005;FitzGerald et al 2008), perceptual and attentional processing during visual encoding (Chuah and Chee 2008), and speed of information processing (Hutchison et al 2001). The theoretical justification for using donepezil in PSA comes for studies demonstrating involvement of the cholinergic system in patients with vascular brain lesions (Mesulam et al 2003;Swartz et al 2003;Sharp et al 2009).…”
Section: Donepezilmentioning
confidence: 99%
“…Across several studies, SD-vulnerable individuals have been found to show greater decline in task-related activation when sleep deprived Chuah and Chee, 2008;Lim et al, 2007). As only correct responses were analyzed in these experiments, trials in which reduced activation could be attributed to volunteers falling asleep were excluded.…”
Section: Functional Utility Of 'Superfluous' Task-related Activationmentioning
confidence: 99%
“…Interestingly, attenuation of brain activation at different task loads (Chuah and Chee, 2008) or levels of perceptual difficulty has been observed even with correct trials, suggesting that a portion of the higher task-related activation observed after a normal night of sleep might correspond to spare information processing capacity. Supporting this hypothesis, maintained or increased task-related activation during SD often corresponds with less compromised or maintained task performance Chee and Choo, 2004a;Drummond et al, 2005).…”
Section: Introductionmentioning
confidence: 99%